Jaringan Transmisi Gardu Induk Sekayu 150 KV - M. Ashof Azria Azka; Mustofa Abi Hamid (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
A substation is a transmission installation that distributes power to a load in a certain area. The Sekayu 150 KV Substation is the center for controlling electrical power load requirements and functions as a center for securing electrical power system equipment and as a center for the normalization process for disturbances in the Sekayu transmission area. The electrical power distribution system does not rule out the possibility of disturbances, especially disturbances caused by nature. If there is an unpredictable disturbance, appropriate and reliable safety equipment (protection system) is needed to be able to increase the distribution of electrical power to the load (consumer).